Production of Sorption Active Polypropylene Fabrics with Sulfonic Acid Groups by Radiation-Induced Modification of Polymer Surface - Bondar, I.V.; Han, D.H.; Cho, H.K. (Хімія, фізика та технологія поверхні, 2010)
Sorption active material carrying sulfonic acid groups was synthesized by radiation-induced graft polymerization of styrene monomer onto the surface of non-woven polypropylene fabric followed by sulfonation of grafted polystyrene chains. The effect of the main experimental parameters on styrene grafting degree (absorbed dose, monomer concentration, reaction time) was investigated. It was found that sulfonation degree of the grafted polystyrene chains with 5% chlorosulfonic acid at room temperature depends on the reaction time and reaches 80% for the samples with a medium value of styrene grafting degree. Sorption active polypropylene fabrics with sulfonic acid group densities of 3.5–5 meq/g were obtained.